The Impact of Non-Judicial Guidance on the Impartiality of Tax Court Judges in Exercising Judicial Power - Andi Ilham Taufik Ramli; Syamsul Bachri; Naswar (IHSA Institute, 2022)
This study aims to analyze the impact of non-judicial coaching on the impartiality of tax court judges in exercising judicial power. This study uses normative legal methods, using a qualitative approach to determine the application of law to the development of tax courts and tax court institutions in Indonesia. The results of this study are (1) Based on the principle of judicial power and the freedom of judges, it implies that judges who serve in the Tax Court must be free from the influence of other powers, but in reality the judges who serve are under the ministry of finance, this is considered to weaken the function supervision and independence of judges in the tax court as a representation of judicial power. (2) The dualism of coaching which shows inconsistency with the existing justice system, causes the tax court not to fully comply with the applicable justice system. In other words, in this condition tax revenue is not completely independent or free from extra judicial influences. So that a political law is needed related to the full statutory tax court under the Supreme Court with the affirmation that the tax court judge must be free from the influence of the power of the ministry of finance.